LAND CERTIFICATION OF LOCAL GOVERNMENT ASSETS FROM COMMUNAL LAND IN WEST SUMATERA - Yontri Faisal, Muhammad Yamin Nasution (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Inventory of local government assets in the form of land are implemented through certification. The purpose of the land asset certification aims to report the financial assets of the government. The land certification aims to secure, inventory, clarity of status, and legal certainty. Land assets Local government in West Sumatra comes from state land, and communal land. Based on the provisions of the first level of land registration of Government Regulation Number 24 of 1997 that communal land is not included in one of the objects of land certification.. The problem in this study is how the implementation of the certification of local government assets derived from communal land in West Sumatra. Problem in this research: how is the implementation of the asset certification of Local Government derived from communal land in West Sumatra. The method in this research is empirical juridical method. Data collection techniques are conducted through structured interviews. The certification of communal land in West Sumatra has no written rules governing it, while local government assets derived from communal lands must be certified, West Sumatra requires a new legal construction because the provisions of land registration have not regulated it. The legal certainty of local government assets derived from communal land will provide a guarantee of security for investors who want to invest in West Sumatera. This will certainly improve the economy and living standards of the people of West Sumatera for the better future.